Features of the defect structure of LiNbO3:Cu crystals and their manifestation in the IR absorption spectrum in the region of stretching vibrations of hydrogen atoms OН– -group - N.V. Sidorov; L.A. Bobreva; M.N. Palatnikov; A.Yu. Pyatyshev; M.K. Tarabrin; A.A. Bushunov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
LiNbO3:Cu (0,005 wt.%), LiNbO3:Cu (0,015 wt.%), LiNbO3:Cu (0,022 wt.%), LiNbO3:Cu (0,042 wt.%), LiNbO3:Cu (0,46 wt.%) crystals were studied by IR absorption spectroscopy in the region of stretching vibrations of OH–-groups. These crystals were grown by the Czochralski method using the technology of direct doping of a charge of congruent composition. It has been established that the recorded absorption bands in the infrared spectrum in the frequency range 3469-3490 cm-1 are associated with a deviation in the composition of the LiNbO3:Cu crystal from the stoichiometric one. Such changes occur due to a deficiency of Li+ cations in the crystal structure. The incorporation of Cu2+ dopant leads to disordering of the cation sublattice and noticeable deformation of oxygen octahedra. This occurs due to an increase in the O–O bond lengths. In this case, a new absorption band with a frequency of 3487 cm-1, corresponding to the VLi-OH complex defect, is recorded in the IR spectrum. Calculation of the volume concentration of OH–– groups showed the highest value for crystals of LiNbO3:Cu (0,005 wt.%), LiNbO3:Cu (0,015 wt.%), LiNbO3:Cu (0,022 wt.%). These changes occur due to the simultaneous formation of two types of complex defects in the crystal structure: Cu+-OH-Cu3- and VLi-OH. A change in the mechanism of entry of a doping impurity into the structure of a LiNbO3:Cu crystal (0,042 wt.%) leads to a decrease in the concentration of OH–– groups.